Empowering Students' Ethnomedicine Literacy through Augmented Reality-Assisted Project-Based Ethnobotany Learning - Gani, Abdul Rasyid Fakhrun; Hastuti, Utami Sri; Sulisetijono, Sulisetijono; Setiowati, Frida Kunti (Universitas Negeri Semarang, 2024)
This research trains the students’ ethnomedicine literacy by using project-based learning and augmented reality assistance and evaluating the learning effectiveness. The research method used was a non-randomized control group pretest-posttest design, and a problem-based learning model was used as a control class. This research evaluates students' ethnomedicine literacy using descriptive statistical data analysis, n-gain scores, and ANCOVA tests. The research results showed differences in ethnomedicine literacy with an ANCOVA significance value of 0.08 between the experimental and control classes. Both classes showed increased ethnomedicine literacy, but the n-gain score for the experimental class was greater than that of the control class. Students' ethnomedicine literacy is higher in the experimental class because there are learning activities that empower ethnomedicine literacy, such as students are trained to be broad-minded, have positive attitudes and behavior related to ethnomedicine studies, working on simple manufacturing projects based on student research to get closer to the environment and society, and using AR as a simulation for testing the antibacterial power of medicinal plants. This research concludes that AR-assisted project-based ethnobotany learning is proven to be able to increase students' ethnomedicine literacy. This research can be helpful as a learning design reference to empower ethnomedicine or other literacy in biology.